Technology diversification, product innovations, and technology transfer - Martin Woerter (ETH Zurich, KOF Swiss Economic Institute, 2009)
This paper investigates the relationship between technology specialization and innovation performance of firms emphasizing technology transfer activities with universities as an important knowledge source in order to attenuate the opportunity costs of technological specialization. Based on an econometric analysis combining patent data and survey data on technology transfer activities of firms it was found that technology transfer is positively related with the sales share of innovative products. Following the technology trajectory (path) increases the probability of an above average innovation performance. Taking into account the combined effects of transfer activities and technological specialization and in this way approximating the idea that transfer activities enable a firm to be specialized and keep the knowledge base broad and uptodate, we detect a significant positive relationship between the combined effect (transfer and specialization) and the innovation performance of a firm. Smaller firms tend to benefit more from the combination of technology specialization and transfer activities with universities compared to larger firms.
Keywords: 330; Innovation; Knowledge and Technology Transfer; Specialization; Diversification; Firms; Innovation; Technologietransfer; Forschungskooperation; Produktdifferenzierung; Schweiz